(3ESHGd GdPjd aj PcQ LjGO GdNjds - (3fLe GdOjf Hf HNjQ GdOjf GdQedjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdNjQ eYbhO HfhGUi GdNjd Edi jhe GdbjGeI s
(3BNQgG (B:s
(3hef CQGO GdJWhjd ai gPG Gdaf aYdjg HcJGH GdehShe HGdbhGYO GdeNHQI hGddg CYde Je GdcJGH HYhf Gdedc GdhgGH GdeSei ESHGd GdPjd ai PcQ LjGO GdNjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HBNQg aGFOIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYI (B507) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs